Using Stylistics To Interpret Literary Texts In The Efl Classroom - Ahlam BOUGUELMOUNA; Halima BENZOUKH (Al-Lisaniyyat, 2021)
Stylistics plays a key role in interpreting pieces of literary writing. It is considered to be the most appropriate and principled approach to study literary texts regarding its comprehensive nature that tries to link two disciplines, linguistics and literary criticism. Focusing on the various linguistic features of texts, stylistics seems to be a powerful tool that- if used properly- can endorse English as Foreign Language (EFL) students to analyze and appreciate literature in all its manifestations in a practical and objective way. The present paper aims at showing the effectiveness of opting for the stylistic analysis in the EFL context. It also attempts to accentuate the significance of the aforementioned approach in facilitating learning literature and making it an enjoyable task for both teachers and learners as well. The overall goal of this research is to investigate whether stylistics is an effective and relevant approach to analyze literary texts.